All theology is natural theology: The hermeneutic necessity of natural theology? - Conradie, EM (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
This article first offers a brief overview of the history of what is understood under “natural theology”. The contrast between the Barthian critique against natural theology and the dangers of repudiating natural theology as stressed within the context of contemporary discourse on science and theology is highlighted. In response, the author offers a constructive proposal in which the hermeneutic necessity of natural theology is affirmed. This follows from a notion of that which is “natural” which includes human constructs (also ideas). In this sense all theology is by definition natural theology. However, the Barthian critique against natural theology may still be appropriate as a selection of those signs that can express the inexpressible with relative adequacy.